A Scoring System for Optimal Selection of Endoscopic Treatment for 1-2cm Lower Pole Renal Calculi - Huang, Yuleng; Li, Kaiwen; Yang, Wenzeng; Li, Zhuohang; Liu, Cheng; Lai, Cong; He, Yongzhong; Xu, Kewei (Urology Journal, 2022)
Purpose: To explore the establishment of a scoring system that can provide a reference for clinical decision making regarding the endoscopic treatment of 1-2 cm lower pole stones (LPS). Materials and Methods: The data of patients with renal calculi who were treated with percutaneous nephrolithotomy (PCNL) or retrograde intrarenal surgery (RIRS) in three hospitals from January 2013 to December 2017 were analyzed retrospectively. Multivariable logistic analysis was performed to determine the statistically significant indicators and regression coefficients, which were used to construct the scoring system. The stone-free rate (SFR) and postoperative complication rates of PCNL and RIRS within the two fractional segments of the scoring system were compared to select the optimal procedures. Results: A total of 137 patients in the PCNL group and 152 patients in the RIRS group were included in this study. Five factors were found to be most predictive of endoscopic treatment choice: stone number, stone diameter, infundibulopelvic angle (IPA), infundibular length (IL), and infundibular width (IW), yielding a total score ranging from 0-5. In the 0-2 segments, the RIRS group had better outcomes than the PCNL group in terms of the postoperative complication rates (6.8% versus 18.0%, P = .026). In segments 3-5, the SFR of the PCNL group was significantly higher than that of the RIRS group (88.5% versus 70.6%, P = .017). Conclusion: Our scoring system was based on the patient’s preoperative imaging examination to measure the stone number, stone diameter, IPA, IL and IW. RIRS was recommended at 0-2 segments, and PCNL was recommended at 3-5 segments. This new scoring system is expected to provide guidance for urologists to make endoscopic treatment decisions for 1-2 cm LPS.